POSSIBILITY OF NATURAL RAW MATERIALS USE IN THE FORMULATION OF ADJUVANT THERAPY OF TUBERCULOSIS: EXPERIENCE OF FOLK MEDICINE, MODERN STATE OF STUDIES - M. E. Kim; K. B. Murzagulova; S. B. Evseeva (Фармация и фармакология (Пятигорск), 2017)
The signs of growth in the prevalence of multidrug-resistant tuberculosis, low effectiveness of therapy indicate the urgent need to solve problems aimed at the improvement of the effectiveness of treatment: the reduction of toxicity and side effects of anti-tuberculosis drugs, the provision of good tolerability and continuity of chemotherapy; the removal of symptoms of intoxication associated with the action of the pathogen on the body, the improvement of the quality of life of patients during therapy and remission.The aim of the investigation is to study the data of folk medicine, scientific research data concerning the use of raw materials of natural (vegetable, animal and mineral) origin in the adjuvant therapy of tuberculosis.Materials and methods. The study was carried out using information retrieval and library databases (PubMed, eLIBRARY, Cyberleninka), technical information of manufacturers of dietary supplements to food, as well as site materials dedicated to the use of vegetable, animal and mineral raw materials in folk medicine.Results and discussion. The adjuvant therapy of tuberculosis includes remedies of natural origin: vegetable, animal and mineral ones. According to the research data, the use of phytotherapy is aimed at enhancing diuresis, which ensures the elimination of toxic substances and their metabolites, as well as the decrease of the overall level of toxins; the strengthening of the body’s antioxidant defense, and liver specificity, the compensation for the increased consumption of vitamins, amino acids and microelements by the liver, which actively metabolizes xenobiotics, as well as the increase of the body’s overall resistance. A long-term benefit of using natural mineral raw materials in adjuvant therapy of tuberculosis is also observed.Conclusion. Thus, adjuvant therapy of tuberculosis includes the use of raw materials of natural (vegetable, animal and mineral) origin, the effectiveness of which is confirmed by laboratory and clinical studies.